ChemInform Abstract: Palladium‐Catalyzed Allylic Arylation of Allylic Ethers with Arylboronic Acids Using Hydrazone Ligands. Issue 32 (18th July 2013) - Mino, Takashi; Kogure, Taketo; Abe, Taichi; Koizumi, Tomoko; Fujita, Tsutomu; Sakamoto, Masami
Abstract The protocol is applied to the preparation of eugenol (XII) which is obtained in moderate yield.